1997
DOI: 10.1021/la960518+
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Atomic Force Microscope Imaging of Calcite Etch Pit Morphology Changes in Undersaturated and 1-Hydroxyethylidene-1,1-diphosphonic Acid Poisoned Solutions

Abstract: Morphology changes in etch pits formed on the (1014) cleavage plane of calcite were induced by varying the ratio of [Ca 2+ ] to [CO 3 2− ] in the bulk solution as well as through the addition of the crystal poison 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP). Three distinct morphologies were noted: symmetric rhombic, asymmetric rhombic, and triangular with a rough curved hypotenuse. The latter represents a transient morphology which is only observed during the actual dissolution process, while the forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…Hillner et al, 1992;Stipp et al, 1994;Liang et al, 1996;Liang and Baer, 1997;Lea et al, 2001;De Giudici 2002) and in the presence of various organic molecules (e.g. Britt and Hlady, 1997;Hong et al, 1997;Teng and Dove, 1997;Teng et al, 1998;Orme et al, 2001 (Davis et al, 2000;Astilleros et al, 2000;Shiraki et al, 2000;Lea et al, 2001;Astilleros et al, 2002;Kamiya et al, 2002;Astilleros et al, 2003;Stipp et al, 2003;Lea et al, 2003;Hay et al, 2003;Godelitsas et al, 2003). While in situ AFM mainly shows the topographic effects of dissolution and growth processes, quantitative information on the subsequent sorption processes can be obtained using surface spectroscopic techniques such as X-ray Photoelectron Spectroscopy (XPS) and Rutherford Backscattering Spectroscopy (RBS) in combination (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hillner et al, 1992;Stipp et al, 1994;Liang et al, 1996;Liang and Baer, 1997;Lea et al, 2001;De Giudici 2002) and in the presence of various organic molecules (e.g. Britt and Hlady, 1997;Hong et al, 1997;Teng and Dove, 1997;Teng et al, 1998;Orme et al, 2001 (Davis et al, 2000;Astilleros et al, 2000;Shiraki et al, 2000;Lea et al, 2001;Astilleros et al, 2002;Kamiya et al, 2002;Astilleros et al, 2003;Stipp et al, 2003;Lea et al, 2003;Hay et al, 2003;Godelitsas et al, 2003). While in situ AFM mainly shows the topographic effects of dissolution and growth processes, quantitative information on the subsequent sorption processes can be obtained using surface spectroscopic techniques such as X-ray Photoelectron Spectroscopy (XPS) and Rutherford Backscattering Spectroscopy (RBS) in combination (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [4,6]. In these studies, the crystal is primarily in a dissolution mode, but the adsorption of impurities at steps and kink sites alters or perturbs the overall dissolution.…”
Section: Article In Pressmentioning
confidence: 99%
“…The crystallography of calcite has been described in several recent publications [1][2][3][4][5][6]. The hexagonal shape of the unit cell is responsible for the rhombic shape of the shallow surface pits that are of interest in the present paper.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies have revealed a dependence of growth kinetics upon parameters such as pH, supersaturation ratio, ionic strength or temperature [2][3][4]. Atomic Force Microscopy (AFM) has been extensively used to study mechanisms and growth rates of single crystals from solution [5][6][7], including calcite crystals [1,[8][9][10][11][12][13][14]. The high resolution of AFM can visualize monomolecular steps on atomically flat crystal surfaces.…”
Section: Introductionmentioning
confidence: 99%